2004
DOI: 10.1097/01.rli.0000119196.50924.f3
|View full text |Cite
|
Sign up to set email alerts
|

T2 Quantitation of Human Articular Cartilage in a Clinical Setting at 1.5 T

Abstract: Our results revealed a clear dependence of apparent T2 relaxation times on the pulse sequence design, emphasizing that the "true" T2 is hard to find. In addition, the effect on the apparent T2 values resulting from the specific modification of any sequence variant varied according to the respective tissue's properties. Therefore, the acquisition technique in conjunction with the specific tissue on which T2 mapping is performed need to be reported in detail and should kept consistent to allow large-scale compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Whereas T2 relaxation time measurements are mainly sensitive to collagen disruption and water content [1218], other techniques exist that are sensitive to GAG concentrations. GAG is largely responsible for the negative fixed-charge density of articular cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas T2 relaxation time measurements are mainly sensitive to collagen disruption and water content [1218], other techniques exist that are sensitive to GAG concentrations. GAG is largely responsible for the negative fixed-charge density of articular cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have reported that patellar undersurface T2 values are affected by activity, OA or BMI [44]. Paralleling the interpretation of elevated/depressed T2 times, there is generally no consensus about normal T2 times, which are reported significantly different between studies [33], which is usually related to varying acquisition and/or post‐processing techniques. Control subjects have to be included into every study to be able to draw intra‐study comparisons, while isolated literary information is sparse as well [20, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Multi echo spin echo, fast spin echo, and the gradient and spin-echo sequences are developed to reduce overall scan time. [54][55][56] T2 relaxation time quantification can be affected by T1 saturation effects, imperfect radiofrequency pulses, static field inhomogeneity, stimulated echoes, and insufficient sampling of the T2 decay points. Therefore, it is essential to select the appropriate T2 mapping protocols and perform proper postprocessing exponential fit when attempting to measure T2 relaxation time.…”
Section: (A) (B)mentioning
confidence: 99%